Pengembangan Bahan Ajar Berbasis Pembelajaran Berdiferensiasi Materi Cerita Tentang Daerahku Kelas IV MIS Al-Jihad Palangka Raya - Muhammad Syabrina; Puan Asmara; Anisa Sofi Anbiya; Ika Wulandari; Wulan Atikaputri (JOURNAL SAINS STUDENT RESEARCH, 2026)
This study aims to develop teaching materials based on differentiated learning on the material of Stories About My Region for fourth grade students of MIS Al-Jihad Palangka Raya. This research is motivated by the use of teaching materials that are still general and have not been able to accommodate differences in abilities, interests, and learning styles of students optimally. The research method used is Research and Development (R&D) with the ADDIE model which includes the stages of analysis, design, development, implementation, and evaluation. Data collection techniques are carried out through observation, interviews, questionnaires, and documentation. Product validation is carried out by material experts and design experts, then tested on teachers and fourth grade students. The results of the study show that the teaching materials obtained a very feasible category with a percentage of validation from material experts of 97.2%, design experts of 93.1%, teacher assessment of 89.4%, and student assessment of 88.2%. The results of the effectiveness test show an increase in student learning outcomes as evidenced by the T test with a significance value of 0.000 <0.05. Furthermore, the N-Gain test results obtained an average of 0.88, categorized as high, and an effectiveness score of 83.19, categorized as effective. Thus, the differentiated learning-based teaching materials for the "Story About My Region" topic are declared feasible and effective for use in the learning process to improve student learning outcomes.